2016
DOI: 10.1103/physrevb.94.241409
|View full text |Cite
|
Sign up to set email alerts
|

Designing an artificial Lieb lattice on a metal surface

Abstract: Recently, several experiments 1,2 have illustrated that metal surface electrons can be manipulated to form a two dimensional (2D) lattice by depositing a designer molecule lattice on metal surface. This offers a promising new technique to construct artificial 2D electron lattices. Here we theoretically propose a molecule lattice pattern to realize an artificial Lieb lattice on metal surface, which shows a flat electronic band due to the lattice geometry. We show that the localization of electrons in the flat b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 40 publications
2
40
0
Order By: Relevance
“…The electrons in the flat band have nearly zero group velocity and their kinetic energy is almost quenched. Thus the Coulomb interaction plays a major role to form some many-body states, such as FM or AF state [39]. Furthermore, these flat bands results in a very large density of states (DOS).…”
Section: Band Structures Of Esdw Statesmentioning
confidence: 99%
“…The electrons in the flat band have nearly zero group velocity and their kinetic energy is almost quenched. Thus the Coulomb interaction plays a major role to form some many-body states, such as FM or AF state [39]. Furthermore, these flat bands results in a very large density of states (DOS).…”
Section: Band Structures Of Esdw Statesmentioning
confidence: 99%
“…For example, Kekulé structure, graphene pn junctions, deformed graphene, graphene nanoribbons, point and line defects, topological domain wall states, Lieb lattice, quasicrystalline structure, and fractal electronics have been realized in molecular designers [23][24][25][26][27][28][29][30]. These systems exhibit exciting physics such as Gauge field, edge states and flat band [35][36][37][38], to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Although the Lieb lattices have been realized in photonic crystals 8,9 and cold atom systems [10][11][12] , creating an electronic version has proved more challenging. Recently, Qiu et al showed that the artificial Lieb lattices can be realized on the metallic copper surface 13 . The artificial Lieb Lattice was rapidly confirmed in experiments 14,15 , providing a realistic electronic Lieb lattice system to explore the above-mentioned physics.…”
Section: Introductionmentioning
confidence: 99%